Wykorzystanie informacji pochodzących z dokumentów tekstowych w problemach modelowania i klasyfikacji - Lula, Paweł (Application of textual data in modelling and classification problems, 2006)
The main subject of this paper is related to text mining analysis. It presents a problem of information retrieval from text documents, information representation, and choice of correct methods of analysis. It was shown that the choice of proper information representation method is the most important stage during research. The paper presents the present abilities of text mining and direction of its development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 130-136